Development and Growth of the Avian Pectoralis Major (Breast) Muscle: Function of Syndecan-4 and Glypican-1 in Adult Myoblast Proliferation and Differentiation - Velleman, Sandra G.; Song, Yan (Frontiers in Physiology, 2017)
Muscle fiber number is determined around the time hatch with continued posthatch muscle growth being mediated by the adult myoblast, satellite cell, population of cells. Satellite cells are dynamic in their expression of proteins including the cell membrane associated proteoglycans, syndecan-4 and glypican-1. These proteoglycans play roles in organizing the extracellular environment in the satellite cell niche, cytoskeletal structure, cell-to-cell adhesion, satellite cell migration, and signal transduction. This review article focuses on syndecan-4 and glypican-1 as both are capable of regulating satellite cell responsiveness to fibroblast growth factor 2. Fibroblast growth factor 2 is a potent stimulator of muscle cell proliferation and a strong inhibitor of differentiation. Proteoglycans are composed of a central core protein defined functional domains, and covalently attached glycosaminoglycans and N-glycosylation chains. The functional association of these components with satellite cell function is discussed as well as an emerging role for microRNA regulation of syndecan-4 and glypican-1.